The Clinical Benefit and Care Burden of Extending the Window of Endovascular Thrombectomy for Stroke in the Emergency Room - Yang, Wookjin (J Clin Neurol, 2019)
BACKGROUND AND PURPOSE: The recent successes of the DAWN and DEFUSE 3 trials have extended the therapeutic time window for endovascular treatment (EVT). Accordingly, an increased care burden and clinical benefit for patients with acute stroke in the emergency room are expected. It is necessary to evaluate and respond to these changes in order to provide the best care to patients. METHODS: Data of patients with acute stroke or transient ischemic attack treated at Seoul National University Hospital between October 2010 and September 2016 were reviewed. To estimate the increased workload associated with the revised guidelines, clinical candidates of acute stroke based on the initial history and examination findings and eligible patients for early stroke intervention were selected. Additionally, the data of eligible patients who received EVT more than 6 hours after the onset were reviewed. RESULTS: The serial addition of intravenous thrombolysis, EVT within 6 hours, and EVT beyond 6 hours to the guidelines resulted in 506 (19.8%), 588 (23.0%), and 718 (28.0%) clinical candidates, respectively, and 329 (12.8%), 365 (14.3%), and 389 (15.2%) eligible patients out of 2,561 patients with stroke. Compared to applying the previous stroke guidelines, the number of clinical candidates increased by 130 (22.1%), whereas the number of eligible patients for early stroke intervention increased by only 24 (6.6%). Seven of the 24 eligible patients received off-label EVT and showed significantly improved neurological outcomes at discharge. CONCLUSIONS: Notwithstanding the small number of subjects in this study, providing EVT to eligible patients beyond 6 hours may improve their neurological outcomes.